New Insight into the ATRP of Monovinyl and Divinyl Monomers. Issue 14 (11th June 2015) - Xue, Xiaoqiang; Wang, Yonglei; Huang, Wenyang; Yang, Hongjun; Chen, Jianhai; Fang, Jianbo; Yang, Yang; Kong, Lizhi; Jiang, Bibiao
<x xml:space="preserve">Abstract</x> New insights are provided into the atom transfer radical polymerizations of styrene with 1, 6‐bismaleimidohexane, tri‐ethylene glycol dimethacrylate (tri‐EGDMA), and divinyl benzene (DVB) as branching agents. Gas chromatography, proton nuclear magnetic resonance spectroscopy, and triple detection size exclusion chromatography are used to analyze the polymerizations and the polymers. The polymerizations and molecular weights of polymers differ because of the different levels of intramolecular cyclization and initiator efficiencies (IEs) among the three polymerization systems. High IE increases polymerization rate and restrains gelation, thereby facilitating preparation of branched polymers with high molecular weights. Polymers in the tri‐EGDMA system exhibit the lowest molecular weight and the broadest polydispersity because of some evident primary chain residues, whereas polymers in the DVB system show the highest molecular weight because of the low amount of the primary chain residues and high IE. The absence of branching monomer units in the primary chain residue of all these polymerizations is confirmed.